NDSHA - The New Paradigm for RSHA - An Updated Review - Bela, J.; Panza, G. F. (Vietnam Journal of Earth Sciences, 2021)
A New Paradigm (data driven and not like the currently model driven) is needed for Reliable Seismic Hazard Assessment RSHA. Neo-Deterministic Seismic Hazard Assessment (NDSHA) integrates earthquake geology, earthquake science, and particularly earthquake physics to finally achieve a New (and needed) Paradigm for Reliable Seismic Hazard Assessment RSHA.Although observations from many recent destructive earthquakes have all confirmed the validity of NDSHA’s approach and application to earthquake hazard forecasting-nonetheless damaging earthquakes still cannot yet be predicted with a precision requirement consistent with issuing a red alert and evacuation order to protect civil populations. However, intermediate-term (time scale) and middle-range (space scale) predictions of main shocks above a pre-assigned threshold may be properly used for the implementation of low-key preventive safety actions, as recommended by UNESCO in 1997. Furthermore, a proper integration of both seismological and geodetic information has been shown to also reliably contribute to a reduction of the geographic extent of alarms and it therefore defines a New Paradigm for TimeDependent Hazard Scenarios: Intermediate-Term (time scale) and Narrow-Range (space scale) Earthquake Prediction.